(untitled) (Conference on English Language Teaching, 2023)
This study was aimed to measure the ability of students in identifying parts of speech in narrative text. It was implemented to students of a public vocational high school) in Bangka Belitung Province. This study utilized quantitative research emphasized in descriptive method in analysing the data. In this study, all of the eleventh grade students from 4 classes which consists of 124 students were taken as the sample. The data were obtained through a test. This study was only focused on five parts of speech including noun, verb, adjective, adverb, and conjunction. It was found that there were 31% of students achieved "good" or B score with the total of 38 students. The accumulation of the entire students’ score or mean of the students’ score was 58. Based on the criteria of the ability stage, it showed that the students’ ability was "fair".